Tra lusso e crisi. Catene del valore, rilocalizzazioni e condizioni di lavoro nel settore moda in Toscana - Redini, Veronica (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
Interest in back-reshoring strategies has gained momentum recently. However, this phenomenon little is known so far about wage and working conditions. This article focuses on plants in Tuscany of luxury global firms that reverse previous off-shoring by bringing manufacturing back home. Drawing on interviews with workers and privileged informants, the article outlines the deterioration of working conditions through the subcontracting relationships of value chain. The main thesis of this paper is that in order to understand the on-going changes there is a need to shows the structural role of interlacement of capital, intangible assets and labour.